Latitudinal patterns of range size and species richness of New World woody plants - Michael D. Weiser; Brian J. Enquist; Brad Boyle; Timothy J. Killeen; Peter M. Jørgensen; Gustavo Fonseca; Michael D. Jennings; Andrew J. Kerkhoff; Thomas E. Lacher Jr; Abel Monteagudo; M. Percy Núñez Vargas; Oliver L. Phillips; et al. (Global Ecology and Biogeography, 2007)
Aim Relationships between range size and species richness are contentious, yet they are key to testing the various hypotheses that attempt to explain latitudinal diversity gradients. Our goal is to utilize the largest data set yet compiled for New World woody plant biogeography to describe and assess these relationships between species richness and range size. Location North and South America. Methods We estimated the latitudinal extent of 12,980 species of woody plants (trees, shrubs, lianas). From these estimates we quantified latitudinal patterns of species richness and range size. We compared our observations with expectations derived from two null models. Results Peak richness and the smallest‐ and largest‐ranged species are generally found close to the equator. In contrast to prominent diversity hypotheses: (1) mean latitudinal extent of tropical species is greater than expected; (2) latitudinal extent appears to be decoupled from species richness across New World latitudes, with abrupt transitions across subtropical latitudes; and (3) mean latitudinal extents show equatorial and north temperate peaks and subtropical minima. Our results suggest that patterns of range size and richness appear to be influenced by three broadly overlapping biotic domains (biotic provinces) for New World woody plants. Main conclusions Hypotheses that assume a direct relationship between range size and species richness may explain richness patterns within these domains, but cannot explain gradients in richness across the New World.